High level of Tregs is a positive prognostic marker in patients with HPV-positive oral and oropharyngeal squamous cell carcinomas - Lukesova, E; Boucek, J; Rotnaglova, E; Salakova, M; Koslabova, E; Grega, M; Eckschlager, T; Rihova, B; Prochazka, B; Klozar, J; Tachezy, R (BioMed research international, 2014)
BACKGROUND: Human papillomaviruses (HPVs) have been proved as one of the etiological factors of oropharyngeal squamous cell carcinoma (OPSCC). Patients with tumors of viral etiology have a lower recurrence rate and better prognosis. OPSCC is linked to an alteration in the immune system. Only a limited number of studies have correlated both the immunological parameters and HPV status with patient prognosis. The aim of this study was to determine whether HPV infection and the immunological status influence patient prognosis individually or in concurrence. MATERIAL AND METHODS: Sixty patients with oral and oropharyngeal carcinomas were enrolled. They were divided into HPV-positive and HPV-negative groups based on the expression of HPV 16 E6 mRNA. Basic lymphocyte subpopulations were determined in the peripheral blood by means of flow cytometry. RESULTS: Significantly better disease-specific survival (DSS) was observed in patients with HPV-positive tumors. Nodal status, tumor grade, recurrence, and CD8+/Tregs ratio were identified as factors influencing DSS. A higher level of Tregs and a lower ratio of CD8/Tregs influenced overall survival (OS) independently of HPV status and age. Patients with HPV-positive tumors and high levels of Tregs survived significantly better than patients from the other groups. CONCLUSION: Better survival is associated with HPV positivity and elevated Tregs levels. Our data suggest that HPV infection and Tregs do not influence patient prognosis in concurrence.
Keywords: Regression Analysis; Carcinoma, Squamous Cell; Female; biologické markery; Age Factors; Biomarkers; inhibitor p16 cyklin-dependentní kinasy; ženské pohlaví; buňky NK; Papillomaviridae; Cyclin-Dependent Kinase Inhibitor p16; věkové faktory; lidé; Survival Analysis; Neoplasm Grading; nádory orofaryngu; regresní analýza; prognóza; stupeň nádoru; proporcionální rizikové modely; Male; T-Lymphocytes, Regulatory; Killer Cells, Natural; Oropharyngeal Neoplasms; spinocelulární karcinom; Proportional Hazards Models; Prognosis; analýza přežití; lidé středního věku; mužské pohlaví; regulační T-lymfocyty; Demography; Middle Aged; demografie; Humans